Validation of the revised child version of the assessment of computer task performance. - Dumont C; Mazer B (Physical & Occupational Therapy in Pediatrics, 2008)
Objective. The purpose of this study was to examine test-retest reliability, internal consistency, and construct validity of the revised child version of the Assessment of Computer Task Performance. The subjects were 155 children of 5 to 11 years of age who did not have any visual or motor impairment. Children 5 through 9 years of age were administered the revised test, which included some additional tasks. Children 10 and 11 years of age were administered selected tasks from the adult version. A subgroup of 52 children were administered the test for the second time to examine test-retest reliability. Intra-class correlations for the mean time to complete two trails indicated moderate to good test-retest reliability (0.66-0.91). The alpha coefficient for tasks administered to children 5 through 9 years of age (0.85) supports internal consistency. Removal of one task increased the alpha coefficient to 0.79 for tasks administered to children 10 and II years of age. Three factors explained 84% of the total variance in scores of children 5-9 years of age and 75% of the variance in scores of children 10 and 11 years of age. The mean time to complete keyboard tasks decreased with age and the mean time to mouse tasks decreased between 5 and 9 years. Conclusion. The results provide evidence of test-retest reliability, internal consistency, and construct validity of the revised Assessment of Computer task Performance.